Resiko Kerja dan Kendala yang Dihadapi Pemadam Kebakaran Kabupaten Indragiri Hilir dalam Melaksanakan Tugas Penyelamatan - Kusumawati, Sri (Indragiri Law Review, 2023)
Firefighters are a job that has high work risks, both the risk of death and the risk of stress after carrying out rescue activities. Apart from that, firefighters also have many risks in carrying out their duties and there are many obstacles in carrying out rescues, especially in Indragiri Hilir district where officers The fire department has quite serious problems in handling fires in residential areas. In the process of making this research the author used a library research method where the data taken was based on books, archival documents and websites. Apart from that, the author also uses qualitative research methods, where research produces data from interviews with several sources, video documentation and photos. Based on this, the author has formulated several problem formulations in writing this journal, namely (1) what work risks are faced by fire brigade personnel in carrying out their duties, (2) what are the obstacles faced by firefighters in carrying out rescue and rescue duties? efforts made by firefighters to prevent fires. And the conclusion from writing this journal is that the work risks faced by firefighters, especially in Indragiri Hilir district, are (1) risk of death, (2) exposure to smoke during the fire process which disrupts health, (3) risk of being exposed to building debris due to the flames. who have reached the roof, (4) the risk of being electrocuted, (5) the risk of exposure to fire which can burn the skin and cause hyperthermia, causing fainting, and also the risk of post-rescue stress. Apart from that, the obstacles faced by Indragiri Hilir district firefighters in working to extinguish the fire include (1) narrow alleys or roads making it difficult for fire trucks to approach the crime scene, (2) the large number of people crowding together which creates road congestion, (3) Slow fire reports from the public to firefighters so that officers are slow to get to the location (4) lack of water sources. And the efforts made to overcome fires include (1) by conducting outreach and education to the public not to burn rubbish at the edge of the house and not to make cigarette butts indiscriminately, (2) by consolidating and coordinating with all parties to work together to prevent fires from occurring. , (3) carrying out simulations for the community to increase public knowledge so that people understand more about dealing with fire disasters